THE EFFECT OF DECOMPRESSION INTENTED INTERVENTIONAL RADJOLOGIC TECHNIQUES ON BILIRUBIN LEVELS IN OBSTRUCTIVE JAUNDICE - Kemal ARDA; Tülay ÖLÇER; Filiz ERYILMAZ ERDİL and Burhan ŞAHİN and Turhan CUMHUR (Turkish Journal of Gastroenterology, 2020)
-